Penguatan Literasi Dan Etika Digital Pada Peserta Didik Dalam Upaya Menanggulangi Hoax Dan Hate Speech - Endang Supriatna; Linda Putri Sari (Universitas Maritim AMNI Semarang, 2023)
One of the most basic and most important things in dealing with the circulation of false information is to strengthen digital literacy and ethics in students, the purpose of this study is to provide education and socialization about the urgency and strengthening of digital literacy and ethics as a preventive in preventing Hoax and Hate Speech information circulating on social media, this study uses descriptive qualitative methods with the results: First, strengthening digital literacy is an effective solution in dealing with fake news circulating, because the higher a person's cognitive abilities, the more selective he is in sorting out the information presented, Second, the implementation stage in strengthening and learning literacy and learning ethics is with various learning methods, especially digital-based learning media, school literacy movements, e-learning and utilization of online learning platforms and applications in honing students' cognitive skills and skills in digital literacy, as well as the effectiveness of socialization about the impact and dangers of hoaxes and hate speech. Third, the obstacles in strengthening digital literacy and digital ethics are student skills, weak parental control and supervision, social and economic status, and the skills and abilities of teachers who are required to continue to innovate.